Фольклор у романі Михайла Стельмаха "Кров людська - не водиця" - Шумада Н. (Народна творчість та етнографія, 2005)
Famous Ukrainian writer of the 20th Century M. Stelmakh had a great interest to Ukrainian folklore not only at the theoretical level. He was working in the Institute of Art Studies, Folklore, and Ethnography as a researcher, which led him to a better understanding of folk’s spirits. He not only widely used folk motifs in his poetry and novels, but created a special atmosphere within his art with the help of folk texts. In the novel "Human’s Blood is not Water" folklore became an important component, which serves a purpose of building up a Ukrainian literary language. The symbolic language, folk poetic forms, folk images serve the purpose in the novel to create a philosophical life approach based on the basic understandings of the human values hidden in a folk lyric songs, humor, epics, legends.